Arbuscular mycorrhizal fungi and salinity stress mitigation in plants - Boorboori, Mohammad Reza; Lackóová, Lenka (Frontiers in Plant Science, 2025)
In recent decades, climate change has caused a decrease in rainfall, increasing sea levels, temperatures rising, and as a result, an expansion in salt marshes across the globe. An increase in water and soil salinity has led to a decline in the cultivated areas in different areas, and consequently, a substantial decrease in crop production. Therefore, it has forced scientists to find cheap, effective and environmentally friendly methods to minimize salinity’s impact on crops. One of the best strategies is to use beneficial soil microbes, including arbuscular mycorrhizal fungi, in order to increase plant tolerance to salt. The findings of this review showed that salinity can severely impact the morphological, physiological, and biochemical structures of plants, lowering their productivity. Although plants have natural capabilities to deal with salinity, these capacities are limited depending on plant type, and variety, as well as salinity levels, and other environmental factors. Furthermore, result of the present review indicates that arbuscular mycorrhizal fungi have a significant effect on increasing plant resistance in saline soils by improving the soil structure, as well as stimulating various plant factors including photosynthesis, antioxidant defense system, secondary metabolites, absorption of water and nutrients.